2016
DOI: 10.3791/54431
|View full text |Cite
|
Sign up to set email alerts
|

Using Touch-evoked Response and Locomotion Assays to Assess Muscle Performance and Function in Zebrafish

Abstract: Zebrafish muscle development is highly conserved with mammalian systems making them an excellent model to study muscle function and disease. Many myopathies affecting skeletal muscle function can be quickly and easily assessed in zebrafish over the first few days of embryogenesis. By 24 hr post-fertilization (hpf), wildtype zebrafish spontaneously contract their tail muscles and by 48 hpf, zebrafish exhibit controlled swimming behaviors. Reduction in the frequency of, or other alterations in, these movements m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 25 publications
0
53
0
Order By: Relevance
“…In comparison, the dystrophic sapje zebrafish moved significantly more than the fkrp -/fish, although their overall distance traveled and velocity were reduced compared with control sibling zebrafish ( Figure 2, B and C). The touch-evoke response assay is another highly reproducible assay to access the overall abilities of a zebrafish larva to move their dorsal muscle in response to a physical stimulus (27,28). Touch-evoke analyses of the fkrp -/zebrafish revealed an overall decrease in response and movement compared with sibling wild-type and heterozygous controls ( Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the dystrophic sapje zebrafish moved significantly more than the fkrp -/fish, although their overall distance traveled and velocity were reduced compared with control sibling zebrafish ( Figure 2, B and C). The touch-evoke response assay is another highly reproducible assay to access the overall abilities of a zebrafish larva to move their dorsal muscle in response to a physical stimulus (27,28). Touch-evoke analyses of the fkrp -/zebrafish revealed an overall decrease in response and movement compared with sibling wild-type and heterozygous controls ( Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…DanioVision zebrafish motion tracking. Five-dpf zebrafish larvae were tracked via the DanioVision (Noldus) motion tracking platform in a protocol slightly modified from a previously published protocol (28). Zebrafish were placed in 48-well plates in 300 ml of fish water and were given a 15-minute acclimation period in the DanioVision machine.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a simple assay for sensorimotor function that consists of eliciting the escape response after tactile stimuli showed that the displacement distance and the average acceleration were no different between wild type and Sarm1 mutants ( Supplementary Fig. 1f, g) 45 .…”
Section: Identification and Mutagenesis Of Sarm1 In Zebrafishmentioning
confidence: 99%
“…Heart rate measurements were performed in triplicate with 10 fish per experiment. Assay of swimming ability, as well as the subsequent data analyses performed on 6 dpf wild type zebrafish treated with increasing doses of L-tyrosine, Tg ACTA1 D286G - eGFP and their control WT siblings treated with 10 ”M L-tyrosine were as per (Sztal et al, 2016). Total voluntary distance travelled in a 10-minute period in the dark was measured in mm using zebraboxes (Viewpoint Life Sciences).…”
Section: Methodsmentioning
confidence: 99%